(3GdeSGgeI GdLfGFjI aj GdLQjeI GdLeQcjI aj GdbGfhf GdLRGFQj (B:s (3OQGSI ebGQfI (B/s - (3eMehO, TGcQ SdjeGfs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdLGeYI GdLOjOI,s, 2017)
(3jJfGhd cJGH (B((3GdeSGgeI GdLfGFjI aj GdLQjeI GdLeQcjI aj GdbGfhf GdLRGFQj (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3TGcQ SdjeGf eMehO(B) (3aj MhGdj (B(194) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bhGfjf hJTQjYGJ GdLeGQc aj GdLRGFQ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3eHMK JegjOj (B: (3acQI YGeI Yf GdeSGgeI GdLfGFjI hGdLQjeI GdLeQcjI, GdaUd GdChd (B: (3GdaGYdhf GdCUdjhf aj GdLQjeI GdLeQcjI, (B... (3EdN(B.s
(3GdCUd CWQhMI eGLSJjQ(B-(3LGeYI GdEScfOQjI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj, (B2015.s
(3HHdjhLQGajI (B: (3UaMI (B181-190.s
Keywords: (3GdLeGQcs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdeSGgeI GdLfGFjIs -- (3GdLRGFQs